Internal Auditing Functions and Their Role in Corporate Governance Systems (gjstudies, 2015)
This research presents a novel, cross-disciplinary framework for conceptualizing the internal auditing function, moving beyond its traditional compliance andfinancial oversight role to position it as the central nervous system of an organization’s corporate governance. Departing from conventional audit methodologies,we propose a bio-inspired, adaptive systems model that draws principles from computational neuroscience, complex adaptive systems theory, and organizational cybernetics. The core innovation lies in reframing internal audit not as a periodiccontrol check, but as a continuous, intelligent sensing and regulatory mechanismembedded within the governance architecture. We formulate and investigate threeprimary research questions: (1) How can principles of homeostasis and allostasisfrom biological systems be operationalized to create a self-regulating, anticipatoryinternal audit process? (2) What is the efficacy of a neural network-inspired auditrisk assessment model that learns and adapts from organizational ’signals’ versus static, checklist-based approaches? (3) Can a simulated, agent-based model ofgovernance interactions demonstrate that an integrated, systemic audit functionimproves resilience to emergent risks? Our methodology employs a hybrid design,combining the development of a theoretical adaptive audit framework with computational simulation using agent-based modeling to test its dynamics. The resultsfrom the simulation experiments indicate that the proposed systemic audit modelsignificantly enhances the detection of non-linear, emergent risks—such as culturaldegradation and strategic misalignment—which are often opaque to traditional audits. Furthermore, the model demonstrates improved organizational adaptationspeed to external shocks by reducing ’governance latency.’ The conclusion assertsthat the most significant contribution of this work is the paradigmatic shift it advocates: internal auditing must evolve from a rear-view mirror function to a forwardlooking, integrative governance sensor, fundamentally altering its design principlesand value proposition. This research opens a new avenue for audit science, onegrounded in the theories of complex systems and biological regulation, with profound implications for how governance structures are engineered in an increasinglyvolatile world